Roger Martin du Gard and Maumort : The Nobel Laureate and His Unfinished Creation - Martin, Benjamin Franklin (Book collections on Project MUSE., 2017)
In the late 1930s and early 1940s, Roger Martin du Gard was one of the most famous writers in the Western world. He won the Nobel Prize for Literature in 1937, and his works, especially Les Thibault, a multivolume novel, were translated into English and read widely. Today, this close friend of Andre Gide, Albert Camus, and Andre Malraux is almost unknown, largely because he left unfinished the long project he began in the 1940s, Lieutenant Colonel de Maumort. Initially, the novel is an account of the French experience during World War II and the German occupation as seen through the eyes of a retired army officer. Yet, through Maumort's series of recollections, it becomes a morality tale that questions the values of late nineteenth- and early twentieth-century European civilization. A fragmentary version of the novel was published in 1983, twenty-five years after its author's death, and an English translation appeared in 1999. Even incomplete, it is a work of haunting brilliance. In this groundbreaking study, Benjamin Franklin Martin recovers the life and times of Roger Martin du Gard and those closest to him.0He describes the genius of Martin du Gard's literature and the causes of his decline by analyzing thousands of pages from journals and correspondence. To the outside world, the writer and his family were staid representatives of the French bourgeoisie. Behind this veil of secrecy, however, they were passionate and combative, tearing each other apart through words and deeds in clashes over life, love, and faith. Martin interweaves their accounts with the expert narration that distinguishes all of his books, creating a blend of intellectual history, family drama, and biography that will appeal to scholars, students, and general readers alike